SEVERE OVARIAN HYPERSTIMULATION SYNDROME (OHSS) – LEADING TO AN INTENSIVE CARE UNIT (ICU) ADMISSION AND NEAR-MISS! SUGGESTED ALGORITHM OF MANAGEMENT WITH CASE REPORT. - Dr Sabahat Rasool, MD, MRCOG, DNB; Dr Qurat Ul Ain, MD; Dr Muzamil Rashid; Prof Shagufta Rather, MD (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Ovarian hyperstimulation syndrome (OHSS) is the most serious iatrogenic complication of ovulation induction. It is characterized by multifollicular, theca-lutein ovarian cysts and an acute shift in body fluid distribution resulting in ascites and pleural and pericardial effusions. Polycystic ovarian syndrome or PCOS is one of the major risk factors for the development of OHSS. We report a case of a 35 year old PCOS patient who was undergoing ovulation stimulation in an IVF (in-vitro fertilization) cycle. 72 hours after egg retrieval, the patient presented to the outpatient department with chief complaints of abdominal pain, nausea, and vomiting. She was admitted for observation and two days later she started complaining of shortness of breath and was found to have developed bilateral pleural effusion and massive ascites. Provisional diagnosis of severe OHSS was made and patient was shifted to ICU for monitoring and started on supportive treatment. She was very hypovolemic and hyponatremic. She was managed with fluid management to maintain intravascular compartment, pain relief, thromboprophylaxis and supportive care and OHSS resolved after one week. In conclusion, although severe complications like pleural effusion are rarely seen in OHSS, prompt diagnosis and successful management is likely to avoid the rapid development of serious life threatening complications.